Quality of Life in Higher Education for Individuals with Intellectual Disabilities and Family Perceptions - Vela, Esther; Henao, Daniela; Serrano, Laura; Martín, Laura (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Intellectual disability is a disorder of intellectual development that, due to its characteristics, involves a series of limitations in cognitive functioning and generalization of learning. These difficulties can evolve with appropriate intervention, which can enhance the quality of life of these people and their families. Objectives: The study seeks to determine the quality of life of people with intellectual disabilities in general and in its different dimensions, taking into account the perception of the person with a disability and that of his/her family. Methods: This study focuses on a specific field: higher education for people with intellectual disabilities. It uses a sample of 19 young people and their 19 corresponding families to determine whether there are significant differences between the two groups, i.e., parents and children. The INICO-FEAPS tool was used to achieve these objectives. Results: The data obtained, and their subsequent analysis have allowed us to detect medium-high levels of quality of life and significant differences between the indices of both groups, highlighting higher scores in the case of families. In addition, self-determination has been revealed as the dimension with the lowest scores, followed by social inclusion and interpersonal relationships. Conclusion: This makes it possible, at the professional level, to focus on these aspects and become aware of the necessary measures to improve intervention in the educational and family environment.